2013
DOI: 10.1007/978-3-642-36958-2_10
|View full text |Cite
|
Sign up to set email alerts
|

Asynchronous Rendezvous Protocol for Cognitive Radio Ad Hoc Networks

Abstract: Abstract. This paper proposes a rendezvous protocol for Cognitive Radio Ad Hoc Networks, RAC 2 E-gQS, which (1) utilizes the asynchronous and randomness properties of the RAC 2 E protocol and (2) grid Quorum System-based channel mapping (gQ-RDV) protocol taking into account channel heterogeneity. We show that the combination of the RAC 2 E protocol with the grid-quorum based channel mapping can yield a powerful RAC 2 E-gQS rendezvous protocol for asynchronous operation in a distributed environment assuring a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…In [18], through the comparison of the MMC [8] with RCA [19] algorithms on a testbed using USRP, it is shown that added asynchronism can have a large beneficial effect reducing the time-to-rendezvous (TTR) 1 . To the best of our knowledge there are only a couple of papers focusing on quorum based asynchronous rendezvous [14], [16], [5], [17]. The references [14], [16], [5], and other above mentioned articles dealing with the asynchronism, do not consider the channel heterogeneity in the generation of channel hopping sequences and asynchronous operation for rendezvous between CRs.…”
Section: Related Workmentioning
confidence: 97%
See 1 more Smart Citation
“…In [18], through the comparison of the MMC [8] with RCA [19] algorithms on a testbed using USRP, it is shown that added asynchronism can have a large beneficial effect reducing the time-to-rendezvous (TTR) 1 . To the best of our knowledge there are only a couple of papers focusing on quorum based asynchronous rendezvous [14], [16], [5], [17]. The references [14], [16], [5], and other above mentioned articles dealing with the asynchronism, do not consider the channel heterogeneity in the generation of channel hopping sequences and asynchronous operation for rendezvous between CRs.…”
Section: Related Workmentioning
confidence: 97%
“…• QS-based protocols for CRNs ( [5], [14], [16], [17]). There are only a few papers considering the asynchronism of the CR nodes during the rendezvous phase.…”
Section: Related Workmentioning
confidence: 99%
“…The CR link layer is provisioning the upper layers and the CE with adequate network resources for control signaling, such as dissemination of spectrum sensing outcomes, spectrum sharing decisions, access to radio environmental databases for retrieving radio context information, etc. This is typically achieved by means of a cognitive control channel [37], [38], selected on the basis of the input by the CE on best suitable primary user channels for control channel establishment, based on historical spectrum sensing decisions and exchanged data.…”
Section: Static Informationmentioning
confidence: 99%
“…Finally, it gives an insight of the performance of the proposed protocol in terms of the timeto-rdv (TTR) 1 and the probability of RDV for the different channel search orders, as well as the inter-rendezvous time variance. Moreover, we evaluate the protocol in a symmetric channel view (homogeneous channel availability) and asymmetric channel view (heterogeneous channel availability, i.e., having different number of idle/unoccupied channels per CR) cases.…”
Section: Eai European Alliance For Innovationmentioning
confidence: 99%
“…However, an asynchronous channel view (ACHv) is not explicitly handled in quorum-based schemes 2 and the channel heterogeneity is not considered in any related work approaches to the best of our knowledge. 1 TTR is an amount of time, measured in slots, within which cognitive radios meet each other once they began hopping, or after the last rendezvous on a channel. 2 Visiting unavailable channels is the most frequently used approaches while dealing with ACHv in the related work (e.g., [18,22]).…”
Section: Related Workmentioning
confidence: 99%